Mitigating Skepticism and Ignorance on the Environmental Protection During Armed Conflict at Sea Within the Legal Systems of Indonesia and Timor Leste - Triyana, Heribertus Jaka; Monteiro, Seguito; Pramesti, Alexandra Mayla (Faculty of Law, Jambi University, 2026)
Marine environmental protection during armed conflict has become a matter of international public concern as escalating tensions among states at sea have caused significant damage to the marine environment. In practice, ambiguity and legal lacunae concerning the applicability of existing rules and regulations governing war at sea have weakened marine environment protection. The superfluous use of weapons, naval platforms, and radioactive substances has increased the attention given by Indonesia and the Democratic Republic of Timor-Leste. This research constitutes normative legal research since the analysis is mainly constructed through scrutiny of state conduct in complying with the law on naval warfare enshrined at the 1949 Geneva Conventions as well as in the San Remo Manual to avoid skepticism and avoidance for their national implementation. It focuses on proportionality, military objectives, and distinctive modes between combatant status at sea and the marine environment as a protected object during armed conflict. Consequently, the applicable rules and regulations provide legal frameworks for analyzing state conduct in addressing the imminent threat of marine environmental damage during armed conflict at sea, an issue to which Indonesia and the Democratic Republic of Timor-Leste are also attentive. This article reveals that clear and robust guidance concerning certain rights and obligations among combatants as well as parties to armed conflict at sea should be derived from principles of international law, including those found in the United Nations Conventions on the Law of the Sea, particularly the principle of due regard, in order to enhance state capacity to control and monitor their conducts. At the same time, the institutionalization of national rules and regulations should be established in practical terms to minimize potential marine destruction within the legal systems of Indonesia and Timor-Leste